2012
DOI: 10.1051/0004-6361/201218898
|View full text |Cite
|
Sign up to set email alerts
|

A close look at the Centaurus A group of galaxies

Abstract: Aims. We study a sample of five dwarf irregular galaxies in the CenA/M 83 group, which are companions to the giant elliptical CenA. We aim at deriving their physical properties over their lifetime and compare them to those of dwarfs located in different environments. Methods. We use archival HST/ACS data and apply synthetic color-magnitude diagram fitting in order to reconstruct the past star formation activity of the target galaxies. Results. The average star formation rate for the studied galaxies ranges fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…We mock-observed these systems from random directions by placing them at a distance of 3.8 Mpc and selecting all luminous galaxies that (1) lie within a cone of opening angle 3.5 • around the host galaxy, (2) are no closer than 0.5 • to the host, and (3) have a distance of less than 800 kpc from the host, mimicking the selection volume of our observed galaxies. The V-band magnitudes M V of the selected Crnojević et al 2010Crnojević et al , 2012Crnojević et al , 2019Müller et al 2017a), and our newly confirmed members (red circles).…”
Section: The Luminosity Function Of Cen a Satellite Systemsupporting
confidence: 54%
See 1 more Smart Citation
“…We mock-observed these systems from random directions by placing them at a distance of 3.8 Mpc and selecting all luminous galaxies that (1) lie within a cone of opening angle 3.5 • around the host galaxy, (2) are no closer than 0.5 • to the host, and (3) have a distance of less than 800 kpc from the host, mimicking the selection volume of our observed galaxies. The V-band magnitudes M V of the selected Crnojević et al 2010Crnojević et al , 2012Crnojević et al , 2019Müller et al 2017a), and our newly confirmed members (red circles).…”
Section: The Luminosity Function Of Cen a Satellite Systemsupporting
confidence: 54%
“…In Fig. 9, we present several of the scaling relations for our newly confirmed dwarf galaxies and compare them to other known Local Group (McConnachie 2012) and Centaurus A dwarf galaxies (Crnojević et al 2010(Crnojević et al , 2012(Crnojević et al , 2019Müller et al 2017a). It is apparent that the Centaurus A dwarf galaxies follow the relations as spanned by the Local Group dwarfs.…”
Section: Scaling Relationsmentioning
confidence: 90%
“…Our luminosity estimate for this object is a lower limit given its disrupting state, and thus the HI mass to light ratio is certainly even lower than the limit we derive, hinting at a genuine lack of gas for this dwarf. Previous HI studies of Cen A early-type satellites only find upper limits of M HI 7 × 10 5 M ⊙ with M HI /L B 0.25M ⊙ /L ⊙,B for this class of objects (Bouchard et al 2007), suggesting that the environment of Cen A is very effective at removing gas reservoirs in these low-mass dwarfs (see also Crnojević et al 2012).…”
Section: Discussionmentioning
confidence: 79%
“…One of the intriguing questions in this context, particularly with respect to dwarf galaxies, is the importance of a galaxy's intrinsic properties ("nature") vs. the importance of external influences ("nurture"). Clearly, both play a role in shaping dwarf galaxies in groups and clusters (e.g., [5,25,28,29,33,42,99,100,68,69,70,71,72,126,128,162]). …”
Section: Re-ionization and Later Environmental Effectsmentioning
confidence: 99%